Counter-terrorism and the rule of law in Malaysia: An analysis of legislative response / How Peng Kwang - How, Peng Kwang (2018)
In this ubiquitous age of terrorism threat facing most nations, the question arises in this study is whether democratic states like Malaysia, India and the United Kingdom (UK) who uphold the concept of Rule of Law, have encouraged or lessened terrorist happenings through their various legislative responses to terrorism. There appears to be a continued worrying trend in not applying the Rule of Law by the courts in Malaysia and its counterparts in India and the UK during a state of emergency. Whilst both countries share similar legal system and process with Malaysia in many aspects, it is further observed that the enacted terrorism legislations were insidious which allow for the circumvention of constitutional and procedural safeguards. Therefore, it is expected that protecting basic human rights is overlooked whenever a democratic nation fights terrorism. Hence, the focus study of these selected jurisdictions seeks to identify and examine the similar pattern of enacted terrorism legislations with considerable impact in these key areas such as, the abnegation of individual human rights; the doctrine of separation of power; judicial activism or restraint towards upholding the Rule of Law; and finally, the impact on the democratic functionality of the States in combating terrorism. The study will also examine what lessons can Malaysia develop from the Indian and UK’s experience in countering terrorism. This research will reveal the values of the Rule of Law have been sacrificed, and it creates undemocratic results not only in Malaysia but in the jurisdictions compared when enforcing counter-terrorism measures. It fails to consider human rights values whenever a conflict in balancing between individual rights and national security arises. iii The interest of the States appears to dominate the constitutional rights of the citizen. The study will conclude that a democratic nation must always uphold the values and respect for everyone which is central to human rights even if that person is an enemy of the State. It is, therefore, indispensable for democratic nations to preserve the tradition of having a respectable legal system. Keywords: Anti-terrorism, National Security, Rule of Law, POTA 2015.